If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3x + -1) + -3(x + 1) = 0 Reorder the terms: 2(-1 + 3x) + -3(x + 1) = 0 (-1 * 2 + 3x * 2) + -3(x + 1) = 0 (-2 + 6x) + -3(x + 1) = 0 Reorder the terms: -2 + 6x + -3(1 + x) = 0 -2 + 6x + (1 * -3 + x * -3) = 0 -2 + 6x + (-3 + -3x) = 0 Reorder the terms: -2 + -3 + 6x + -3x = 0 Combine like terms: -2 + -3 = -5 -5 + 6x + -3x = 0 Combine like terms: 6x + -3x = 3x -5 + 3x = 0 Solving -5 + 3x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 3x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + 3x = 0 + 5 3x = 0 + 5 Combine like terms: 0 + 5 = 5 3x = 5 Divide each side by '3'. x = 1.666666667 Simplifying x = 1.666666667
| 3x-2y-3z+7x-5y+9z= | | (x-34)= | | 6-x=3-4 | | a*3=15 | | (P-4)(2)=16 | | 4n^2+12n=160 | | 7x(2)-6=57 | | 4(x+3)=5x+3 | | 15=8x+7 | | -5qr*(-7pr^3)= | | 20x+7=127 | | 4x(2)-6=74 | | 4n^2-7=249 | | M(2)+7=6 | | 6x^2-5=481 | | B(2)=34 | | A(2)+1=2 | | 8km^2p*3mn^3= | | 3n^2-10=17 | | X(2)=29 | | 3x-4y+2z+5x+2y-3z= | | R(2)=96 | | 2cd*cd= | | 4x+3+8-3x=-2x+6x-2 | | 30x+4=244 | | 3p^2+10=310 | | 4hk*5st= | | 3mn*9m= | | 2,5/x=8/3 | | 2x+3y+0.1z=100 | | 7x-3y+2x-10y= | | 4x-24=3x+36 |